Performance of Natural Ventilation in Residential Buildings under Different Opening Conditions - Fisa Savanti; Hari Utama; Hanif Ardhiansyah (Sainteknol : Jurnal Sains dan Teknologi, 2025)
Natural ventilation is widely applied in tropical residential buildings to improve indoor environmental quality and reduce cooling energy demand. However, increasing opening size does not always proportionally enhance ventilation performance. This study aims to experimentally determine the relationship between inlet opening variation and natural ventilation performance in a residential test room (6.0 m × 2.5 m × 3.5 m; 52.5 m³) oriented along the Southwest–Northeast axis. The investigation was conducted by measuring variations in indoor air velocity, temperature, relative humidity, and estimating the air change rate (ACH) under different inlet opening conditions. The inlet door opening was varied from 20% to 100%, while the outlet door remained fully open. Results indicate a non-linear relationship between opening variation and ventilation performance. Indoor air velocity increased from 0.09 m s⁻¹ at 20% opening to a maximum of 0.11 m s⁻¹ at 60%, then decreased at larger openings. ACH followed a similar trend, peaking at the intermediate configuration. Temperature differences remained minimal, confirming the dominance of wind-driven airflow, while relative humidity varied with airflow distribution and dilution effects. The findings suggest that moderate inlet openings may provide more efficient ventilation than fully open configurations in tropical residential buildings.